Agglomeration economies and urban productivity - Tania Paola Torres Gutierrez; Jessica Andrea Ordó\~nez (REGION, 2019)
This study explores the relationship between agglomeration economies and industrial productivity between 1980 and 2010 in Ecuador. The measure of productivity used is labour productivity. We conclude that urbanization economies have a positive impact on productivity in the period analyzed.
Keywords: R12; 330; agglomeration; agglomeration economies; urban productivity; Ecuador